Genetic diversity and distribution patterns of diploid and polyploid hybrid water frog populations (Pelophylax esculentus complex) across Europe. Issue 17 (26th August 2015) - Hoffmann, Alexandra; Plötner, Jörg; Pruvost, Nicolas B. M.; Christiansen, Ditte G.; Röthlisberger, Sandra; Choleva, Lukáš; Mikulíček, Peter; Cogălniceanu, Dan; Sas‐Kovács, István; Shabanov, Dmitry; Morozov‐Leonov, Svyatoslav; Reyer, Heinz‐Ulrich
Abstract Polyploidization is a rare yet sometimes successful way for animals to rapidly create geno‐ and phenotypes that may colonize new habitats and quickly adapt to environmental changes. In this study, we use water frogs of the Pelophylax esculentus complex, comprising two species (Pelophylax lessonae, genotype LL; Pelophylax ridibundus, RR) and various diploid (LR) and triploid (LLR, LRR) hybrid forms, summarized as P. esculentus, as a model for studying recent hybridization and polyploidization in the context of speciation. Specifically, we compared the geographic distribution and genetic diversity of diploid and triploid hybrids across Europe to understand their origin, maintenance and potential role in hybrid speciation. We found that different hybrid and parental genotypes are not evenly distributed across Europe. Rather, their genetic diversity is structured by latitude and longitude and the presence/absence of parental species but not of triploids. Highest genetic diversity was observed in central and eastern Europe, the lowest in the northwestern parts of Europe. This gradient can be explained by the decrease in genetic diversity during postglacial expansion from southeastern glacial refuge areas. Genealogical relationships calculated on the basis of microsatellite data clearly indicate that hybrids are of multiple origin and include a huge variety of parental genomes. Water frogs in mixed‐ploidy populations without any parental species (i.e. all‐hybrid populations) can be viewed as evolutionary units that may be on their way towards hybrid speciation. Maintenance of such all‐hybrid populations requires a continuous exchange of genomes between diploids and triploids, but scenarios for alternative evolutionary trajectories are discussed.